The Use of Dried Tomato Pulp in Diets of Laying Hens - Jafari, Massoud; Pirmohammadi, Rasoul; Bampidis, Vasileios (International Journal of Poultry Science, 2006)
In an experiment with 288 laying hens from a commercial strain (Hy-line W36), the effect of partial and total replacement of soybean meal, corn grain, wheat grain and wheat bran with dried tomato pulp (DTP) on performance and egg quality was determined. In the 12 week experiment, hens (27 to 38 weeks of age) were allocated to four dietary treatments being: DTP0, DTP50, DTP100 and DTP150 of 72 birds each, and received a diet ad libitum. The diet for DTP0 treatment had no DTP (control), while those for treatments DTP50, DTP100 and DTP150 included 50, 100 and 150 kg/t of DTP, respectively. Inclusion of DTP at levels up to 100 kg/t in diets of laying hens increased egg production and egg mass by 2.7% and 4.1%, respectively, compared to the control and resulted in similar traits, relative to final BW, egg weight, daily feed consumption, egg shell weight, egg shell thickness, haugh units and yolk color. However, inclusion of DTP at higher level (150 kg/t of diet) decreased egg production and egg mass by 3.6% and 3.0%, respectively, and increased feed efficiency by 2.9% compared to the control. Thus, DTP can be used as an alternative feedstuff in laying hen diets, at inclusion levels up to 100 kg/t without negative effects on performance and egg quality.